\(\frac{x}{2}=\frac{y}{3}\)
\(\Rightarrow\frac{2x}{4}=\frac{3y}{9}\)
áp dụng tính chất của dãy tỉ số bằng nhau ta có :
\(\frac{2x}{4}=\frac{3y}{9}=\frac{2x-3y}{4-9}=\frac{1}{-5}\)
tự lm tp
\(a)\frac{x}{2}=\frac{y}{3}\) và \(2x-3y=1\)
Ta có: \(\frac{x}{2}=\frac{2x}{4};\frac{y}{3}=\frac{3y}{9}\)
Mà: \(\frac{x}{2}=\frac{y}{3} \implies \frac{2x}{4}=\frac{3y}{9}\)
Áp dụng tính chất dãy các tỉ số bằng nhau ta có:
\(\frac{2x}{4}=\frac{3y}{9}=\frac{2x-3y}{4-9}=\frac{1}{-5}\)
Suy ra: \(\frac{x}{2}=\frac{1}{-5}\implies x=\frac{1.2}{-5}\implies x= \frac{-2}{5}\)
\(\frac{y}{3}=\frac{1}{-5}\implies y=\frac{1.3}{-5}\implies y=\frac{-3}{5}\)